AS NOVAS TECNOLOGIAS NA SALA DE AULA: A APROPRIAÇÃO DOCENTE DAS NOVAS TECNOLOGIAS EM SUAS DIDÁTICAS - Santos, Fernanda dos (2015)
This study aims to analyze how teachers of the state school called “João Rodrigues”, from the public high school network of the city of Areia, state of Paraíba, are appropriating themselves to the new technologies in their teaching process. Our theoretical basis is rooted in the literature review of Kenski (2007), Lévy (1999), Moran (2006), Gadotti (2003), among others. Data collection instruments used in the research were non-participant observation in classroom, semi-structured questionnaire consisting of 9 questions to 9 male and female teachers and focus group, targeted 16 boys and girls, composed of a structured interview script. Data were divided by study themes distributed as: what technologies male and female teachers use in their classroom; educational use of technological resources by male and female teachers; problems encountered by these teachers in the use of these resources; reception of pupils to the use of new technologies in classroom. From the data, it is concluded that ownership of resources by teachers is still under development; teaching use of these technologies is restricted to some feature's functionality, showing then difficulties to find these technological resources at school. Another important aspect was the lack of teaching approach between male and female students, who, for the most part, pointed out as major challenges: the lack of these resources at school, inadequate preparation of the teachers, as well as a distance of the teachers regarding to the students.